A retrospective review of language brokers’ coping and emotional responses - Santamaría Ciordia, Leticia (Estudios de Traducción, 2026)
Child language brokering (CLB) is too varied to be portrayed as a solely positive or negative psychological experience, which provides at least a partial explanation for the mixed findings in the extant literature about the effects of CLB on bilingual children.A corpus of approximately eight hours of semi-structured interviews with thirty former child language brokers from different countries allows the author to reflect on potential stressors that could ultimately help to predict children’s emotional responses, coping skills and psychological adaptation to challenging settings.The study revealed two parameters that may predict potentially stressful situations and negative outcomes arising from CLB: 1. awareness of the consequences of mistranslations (game vs. responsibility), and 2. language brokers’ mixed maturity, i.e. the ability to handle exposure to cognitive situations and challenges they may lack the emotional skills for. These two variables, along with other potential stressors, such as the complexity, severity or unease with the situation, makes them potentially vulnerable and might explain conflicting emotions when translating in adult situations, such as the coexistence of feelings of self-worth with feeling overburdened.The conclusions draw attention to avoiding the premature assigning of translating responsibilities before children are emotionally or developmentally ready, an approach worth considering as many immigrant families still prefer to ‘trust’ their own children as linguistic mediators, even when professional interpreters may be available.